Performance Investigation of Dual Wavelength Fiber Laser using different SOAs - Ong, Y. S.; Sulaiman, A. H.; Abdullah, F; Lau, K. Y.; Yusoff, N. Md. Yusoff (International Journal of Integrated Engineering, 2020)
We investigated the performance of a dual wavelength fiber laser (DWFL) using different types of semiconductor optical amplifiers (SOAs) utilizing fiber Bragg gratings (FBGs) as comb filter. The lasing performances of linear SOA (LSOA), nonlinear SOA (NLSOA) and booster optical amplifier (BOA) at different current setting were observed. LSOA produced the flattest spectrum based on its peak power difference at only 4.5 dB as compared to 66.4 dB using BOA. BOA has the worst flatness because its polarization sensitivity is the highest as compared to LSOA and NLSOA. Overall, the best lasing performance is when LSOA is used due to the lowest peak power difference with high peak power at -17.6 dBm.